Frequency and risk factors of restless leg syndrome in pregnant women - Zainab Memon; Nusrat Nisar; Bakhtawar; Rabia; Ghazala; Sidra (Journal of Shalamar Medical & Dental College)
Background: Restless leg syndrome (RLS) is a prevalent neurological condition in pregnancy, and is associated with poor maternal and fetal outcomes